Anesthesia management of patients undergoing off-pump coronary artery bypass grafting: A retrospective study of single center - Lin, Yong; Sun, Tao; Cheng, Ning-ning; Liu, Jing-jing; He, Li-xian; Wang, Li-hong; Liu, Xian-wen; Chen, Mei-fang; Chen, Liang-wan; Yao, Yun-tai; , the Evidence in Cardiovascular Anesthesia (EICA) Group (Frontiers in Surgery, 2023)
Background To summarize the current practice of anesthesia management for Chinese patients undergoing off-pump coronary artery bypass (OPCAB) surgery at a large-volume cardiovascular center. Materials and methods The clinical data of consecutive patients undergoing isolated, primary OPCAB surgery during the period from September 2019 to December 2019 were retrospectively analyzed. Patient characteristics, intraoperative data, and short-term outcomes were extracted from the Hospital Information System and the Anesthesia Information Management System. Results A total of 255 patients who underwent OPCAB surgery were enrolled in the current study. High-dose opioids and short-acting sedatives were the most commonly administrated anesthetics intraoperatively. Pulmonary arterial catheter insertion is frequently performed in patients with serious coronary heart disease. Goal-directed fluid therapy, a restricted transfusion strategy, and perioperative blood management were routinely used. Rational usages of inotropic and vasoactive agents facilitate hemodynamic stability during the coronary anastomosis procedure. Four patients underwent re-exploration for bleeding, but no death was observed. Conclusions The study introduced the current practice of anesthesia management at the large-volume cardiovascular center, and the short-term outcomes indicated the efficacy and safety of the practice in OPCAB surgery.